Pathogenicity Prediction of Potential Variants in TULP1 Gene causing Hereditary RP: An In-silico Approach - Sadiq, Faryal (Current Trends in OMICS, 2024)
Retinitis Pigmentosa (RP) is a term used to describe a group of eye disorders related to retina damage. Due to the formation of bone spicules inside the retina of the affected individuals, patients suffer from poor eye vision or complete blindness, rarely. The reason of the disease could be genetic defects or environmental factors, for instance comorbidity, light exposure, and ethnicity. Tubby-like protein (TULP1) is expressed in the retina of the eye, specifically inside rod and cone cells, and mutations inside the gene can cause changes in structure and function of photoreceptor cells. The current study may provide new insights to understand the genetic variations found in TULP1 gene from the genomic to proteomic level, thus predicting the highly pathogenic variations causing RP. Different bioinformatic tools employing different algorithms were used to score the pathogenic variants, hence cross validating the results. Twenty (20) pathogenic missense variants which can destroy the protein structure as discussed in the study, thirteen (13) splice site variants, and lastly, nine (9) frameshift, seven (7) stop-gained variants were concluded as highly pathogenic for the candidate gene.